DIGITAL SPIRIT SIDOLUHUR (DSS) DALAM MEMBANGUN IDENTITAS DAN DAYA SAING SEKOLAH DESA - Jaya Bhaharuddin Yusuf; Mohamad Joko Susilo (Jurnal Manajemen Pendidikan, 2026)
Objective: The rapid development of digital technology requires rural schools not only to adapt to digital media but also to strengthen their institutional identity and competitiveness. This article aims to analyze and formulate the Digital Spirit approach as a digital empowerment model for strengthening rural school branding. This study employs a qualitative approach using a literature review method, examining relevant studies on digital literacy, educational branding, and school community empowerment. The findings indicate that the Digital Spirit approach emphasizes the integration of digital literacy development among school members, community participation, and the strategic use of digital media as a means of communicating school values and identity. This model promotes not only technical digital readiness but also the construction of an adaptive, participatory, and competitive image of rural schools. The study contributes a conceptual model for rural school branding based on digital empowerment that can be adapted by educational institutions in similar contexts.